Effectively designed NTW shell-tube heat exchangers with segmental baffles using flow hydraulic network method. (25th June 2017) - Tahery, Amir Asgari; Khalilarya, Shahram; Jafarmadar, Samad
Highlights: Using flow hydraulic network model is an alternative design method. NTW design technique improve the original design heat transfer performance. Reduce the original design pressure drop by removing window-section tubes. NTW design technique reduce the original design exergy destruction rate. Abstract: In the present study, performance analysis of a shell-tube heat exchanger by using hydraulic network modeling has been employed in order to enhance the performance of the heat exchanger. Since a major component of a shell-tube heat exchanger is tubes, the aim of this paper is to study the effect of using different tube count, tube layout and tube diameter at different baffle sections on heat transfer, pressure losses and exergy destruction rate of shell-tube heat exchangers with segmental baffles. Three different modified designs with a classical design of a specimen shell-tube heat exchanger have been taken into consideration for their thermo-hydraulic performances and the results are compared. It is revealed that the modified heat exchanger, even though the number of tubes is reduced compared to the conventional design version, has better thermo-hydraulic performance, improving the original design heat transfer performance, and having lower exergy destruction rate. Eliminating window section will allow the cross and window flow to mix better and will automatically increase the heat transfer performance. The results obtained from the present method show that by elimination window-section baffles, heat transfer performance (hs /ΔPs ) increased about 25–48% at different mass flow rates. Also for a shell-tube heat exchanger requiring low pressure drop No Tube at Window section design (NTW) is an alternative. So application of NTW shell-tube heat exchangers is recommended and the results of these methods are directly applicable to real design. Also using this method provides the necessary database to refine the previous empirical flow rate methods for use in the prediction of the instabilities of industrial heat exchanger tube bundles.